Analysis of Slang Words Used for Comments on Tiktok - Eka Fanti Sulistiyaningsih; Nurul Muttaqiyah (Universitas An Nuur, 2022)
This research in title “Analysis of Slang Words Used for Comments on Tiktok”. The aim of this research are to analyze slang words on Tiktok and to find out the meaning of these slang. This study is included in descriptive qualitative method. In collecting data, the writer concentrates the comments which contains the slang words produced by netizens. After the researcher analyzed the data, it shows that slang is used for entertainment, just joking/funny, looks contemporary, reduces seriousness in speaking and softens satire. Therefore, research on slang will be able to continue from time to time as a sign that language tends to change.